Management of Seeding Rate and Nitrogen Fertilization for Lodging Risk Reduction and High Grain Yield of Mechanically Direct-Seeded Rice under a Double-Cropping Regime in South China - Longmei Wu; Keru Yu; Jixiang Zou; Xiaozhe Bao; Taotao Yang; Qingchun Chen; Bin Zhang (Agronomy, 2024)
Precision hill-drop direct seeding using mechanical drilling is a unique direct seeding technique employed in south China that offers advantages such as excellent grain yield and high lodging resistance. Improving yield and lodging-related traits is essential for efforts to improve mechanically direct-seeded rice (MDSR) production. Seeding rates (SR) and nitrogen (N) fertilization rate are two of the main factors affecting grain yield and lodging resistance under MDSR production. However, little information about double-season MDSR production in south China is available. Here, we evaluated yield and lodging risk for two rice cultivars Huanghuazhan, HHZ, lodging-resistant; Xiangyaxiangzhan, XYXZ, lodging-susceptible across two consecutive growing seasons under two under two seeding rates (LSR, 30 cm × 18 cm; HSR, 30 cm × 12 cm) and three N fertilization rates (N1 = 100 kg ha−1, reduced N; N2 = 150 kg ha−1, normal N; and N3 = 200 kg ha−1, enhanced N). We found that increased SR and N fertilization rate improved grain yield and increased lodging risk. SR and N were consistently and positively related to plant height (PH), gravity center height (GCH), the length from the broken basal internode to the panicle tip (SL), the fresh plant weight of the plant part above the broken point (FW), and the length of the two basal internodes. SR and N decreased breaking force (F) and breaking strength (BM), driving increased lodging risk as reflected by increases in lodging index (LI) values. Culm diameter (CD) and culm wall thickness (CWT) did not respond consistently to SR and N treatments. Correlation analysis revealed that PH, GCH, the length of first and second basal internodes, FW, and bending moment for the whole plant (WP) were positively correlated with LI, while F and BM were negatively associated with LI. These findings suggest that the increased lodging risk resulting from high SR could be mitigated by applying appropriate rates of N; that is, this work suggests that grain yield can be maximized and lodging risk minimized by increasing SR while decreasing N fertilization rate. Seasonal differences in the effects of SR and N fertilization should be considered to achieve a high grain yield and maintain high lodging resistance. Our study suggests that increasing SR and decreasing N fertilization can enhance rice grain yield while improving lodging resistance for both varieties. Optimizing grain yield by increasing SR while reducing lodging risk by lowering N application rates may maintain lodging resistance and improve grain yield.